Pengaruh Permainan Ular Tangga Edukatif Terhadap Hasil Belajar Anak Usia Dini - Mita Sari; Nur Apni; Fitriani AR. Latoko; Fikra Mahyun (INDO PUBLISHING, 2026)
This study aims to determine the effect of the educational Snakes and Ladders game on the learning outcomes of early childhood children. The study used a quantitative approach with an experimental method using a one-group pretest-posttest design. The study subjects were 20 children in Group B, aged 5–6 years, at an early childhood education institution (PAUD). Data collection techniques included observation, documentation, and learning outcome tests before and after the implementation of the educational Snakes and Ladders game. Learning outcome indicators included number recognition, letter recognition, learning concentration, cooperation, and simple problem-solving skills. The results showed an improvement in children's learning outcomes after the implementation of the educational Snakes and Ladders game. The average pretest score of 58.4 increased to 85 in the posttest, representing an increase of 26.6. The educational Snakes and Ladders game has been proven to create an active, fun, and interactive learning environment, resulting in more enthusiastic participation in learning. Therefore, the educational Snakes and Ladders game has a positive effect on the learning outcomes of early childhood children.